Surgical treatment for chronic Charcot neuroarthropathy. (September 2018) - Galli, Marco; Scavone, Giuseppe; Vitiello, Raffaele; Flex, Andrea; Caputo, Salvatore; Pitocco, Dario
Highlights: Charcot neuro-arthropathy (CN) is a condition characterized by a progressive derangement of the joints, in individuals affected with sensitive and autonomic neuropathy. CN is a well know dilemma in the management of the diabetic foot. There is no uniformity in the clinical and surgical care of this condition, and the treatment is often left to the surgeon's experience. There are several surgical procedures accepted in Charcot foot surgery. Their goal is to obtain a plantigrade foot and prevent recurrent ulcerations. Arthrodesis is a surgical procedure that addresses severe joint derangement through a surgically induced bony fusion. In Charcot foot, arthrodesis is usually indicated when there is significant skeletal instability. Patients may eventually undergo a major amputation because of comorbidities, residual intractable deformity, infection, recurrent ulcers. Abstract: Charcot Neuro-arthropathy (CN) is a condition characterized by a progressive derangement of the joints, in individuals affected with sensitive and autonomic neuropathy. The pathogenesis of CN is multifactorial as neuropathy is a necessary, but insufficient condition for the onset of the disease. The most important indication for surgical treatment of Charcot foot is a severe deformity that compromises the functionality of the limb, causing a high risk for ulceration, infection and amputation. The goal in Charcot foot treatment is to obtain and maintain the correction of a severe deformity and/or prevent its development. There are many surgical approach to the CN, such as exostectomy, arthrodesis with internal or external fixation and amputation. Every method has a different indication and specific complication. The right surgical approach in the CN is a real challenge for orthopedic surgeon that need a complete knowing of technique, material and complication.